Laicidad del estado ¿hay una separación definitiva entre la iglesia católica y el estado colombiano? (2012)
Relations between the Catholic Church and the Colombian government have had a number of approaches, which are expressed according to the historical moment in the evolution of our Republican trend. This paper presents the conflicts that have aroused from the Concordat of 1973 to the present time. This study aims not only to account for the situation in which the Concordat was left, but for the current situation of the relations between the Colombian government and the Catholic Church from the 1991 Constitution and all its legal and institutional development. Such intention takes shape through a line of cases from landmark judgments that served as the basis for the current trend governing the relations between the institutions already mentioned, which also involves the panorama of other churches and religions established in Colombia, as a third party ad excluendum seeking for a principle of equality in the new constitutional relations.